Antropologia ed educazione tra ricerca e azione sul territorio. Esperienze con i popoli indigeni in Brasile - Gomes, Ana Maria R. (Antropologia Pubblica, 2024)
For over twenty years, indigenous students, sapiens, shamans, along with experts holding specific knowledge, and political leaders have been continuously present and active in the University. These presences gave place to (exemplary) ethnographic scenes, hereby reported in dialogue with statements of political, cosmopolitical and epistemological nature about knowledge practices that involve different people, and different cultural traditions. Focusing either on knowledge practices that occur during meeting and training in the university, or on similar interactions regularly carried out in indigenous territories, the paper explores the arrangements and adjustments of relationships between different indigenous people and communities. In addition, by looking at the training programs for indigenous teachers, it aims to highlight the core intentions of educational public policies, and to explore the conceptual shifts and suspensions of meaning that destabilize what we can assert about the manners and meanings of “our knowledge”, as produced in relation with different indigenous partners.